2004
DOI: 10.1182/blood-2004-04-1389
|View full text |Cite
|
Sign up to set email alerts
|

Combination of intensive chemotherapy and imatinib can rapidly induce high-quality complete remission for a majority of patients with newly diagnosed BCR-ABL-positive acute lymphoblastic leukemia

Abstract: for the Japan Adult Leukemia Study GroupThe outcome for adult patients with BCR-ABL-positive acute lymphoblastic leukemia (ALL) remains dismal and long-term survival can hardly be achieved except by allogeneic hematopoietic stem cell transplantation (HSCT). The Japan Adult Leukemia Study Group (JALSG) has recently started a phase 2 trial with intensive chemotherapy and imatinib for newly diagnosed BCR-AB-positive ALL patients, and we present here the interim results for the first 24 patients. All patients exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(109 citation statements)
references
References 32 publications
(47 reference statements)
7
99
2
1
Order By: Relevance
“…Importantly, patients with Ph-positive ALL are now treated with imatinib-containing regimens in specific studies that appear to highly improve the outcome of these high-risk patients. [41][42][43] Otherwise, the choice between ASCT or chemotherapy is still open. One may consider that the use of ASCT significantly reduces the total duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, patients with Ph-positive ALL are now treated with imatinib-containing regimens in specific studies that appear to highly improve the outcome of these high-risk patients. [41][42][43] Otherwise, the choice between ASCT or chemotherapy is still open. One may consider that the use of ASCT significantly reduces the total duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in these treatment modalities [1][2][3][4][5][6][7][8] have resulted in a growing number of acute leukemia survivors. Allo-HCT is a potentially curative treatment strategy that reduces the risk of relapse, however, it carries an attendant risk of significant acute complications and late effects that may lead to non-relapse mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Imatinib is started at a dose of 300 mg/day and continued into consolidation and maintenance phase. Several studies [18][19][20][21] have reported increased CHR with the addition of imatinib to chemotherapy regimen. Our study results also show a high CHR rate of 77 % (10/ 13) with use of imatinib in induction regimen.…”
Section: Discussionmentioning
confidence: 99%